Інтродукційні дослідження рідкісних видів рослин у Кременецькому ботанічному саду - Lisnichuk, A.M.; Onuk, L.L.; Chubata, T.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
More than two centuries ago the Kremenets Botanical Garden started scientifically based plant introduction, including a large group of rare species. The authors’ task is to make a comprehensive analysis of the rare plants collection of the Kremenets Botanical Garden and to exclude perspective species for their use in the reintroduction in order to support the quantity of destructive and formation of duplicating populations of rare and endangered species within their natural habitat. The rare plants collection includes 140 species of different conservation status, of which 40 are known in the Kreme nets Mountains’ flora. Groups of plants growing in the collection have different ecomorphs with the predominant share of sun-loving mesophytes represented mainly by perennial grasses typical of meadow and meadow- steppe communities. Due to the results of the research introduced species from perspective and particularly perspective groups are excluded. The key figures of their life condition indicate success of the introduction. Perspective and particularly perspective species, which by origin are representatives of the Kremenets Mountains’ flora, is valuable potential material for reintroductive studies in natural biocenoses.